Improvement of Construction Project Management Processes - Nazarko, J. (Journal of Engineering, Project, and Production Management, 2017)
The common denominator of the five papers published in the current edition of the Journal of Engineering, Project, and Production Management is the improvement of construction project management processes for effective use of resources. Execution of proper project management processes is widely recognized as a key success factor influencing likelihood of project success (Alleman, 2014). It is noticeable that four out of five papers in this issue of the Journal are authored or co-authored by Iranian researchers from the same Institute but their conclusions bear importance that cannot be limited to the authors’ region.